Analisis Yuridis Undang-Undang Tabungan Perumahan Rakyat Ditinjau Dari Perspektif Good Governance - Tazkiya Amalia Nasution (Universitas Islam Indonesia, 2021)
The ratification of the implementation of Law Number 4 of 2016 concerning the Implementation of Public Housing Savings or called the TAPERA Law on May 20, 2020, however caused pros and cons from the community. The objectives to be achieved in this research are, first, to find out the management of funds under the Tapera Law and the benefits of implementing the Act. Second, to find out the urgency of the ratification of the Tapera Law on affected legal subjects in terms of the achievement of Good Governance. This research is juridical normative with a statutory approach and a concept approach. The results of this study conclude that, first, the management of the Tapera Law begins with three stages, namely the mobilization of funds, the accumulation of funds, and the use of funds. Second, the lack of achievement of several principles in the realization of the implementation of Good Governance in the Tapera Law has resulted in the need for the implementation of the law.Keywords: Good governance; legal policy; public house savings lawAbstrakPengesahan pelaksanaan Undang-Undang Nomor 4 Tahun 2016 Tentang Penyelenggaraan Tabungan Perumahan Rakyat atau disebut dengan UU TAPERA pada 20 Mei 2020 lalu, akan tetapi menyebabkan adanya pro dan kontra dari masyarakat. Tujuan yang ingin dicapai dalam penelitian ini yaitu, pertama, untuk mengetahui pengelolaan dana UU Tapera diberlakukan dan manfaat dijalankannya UU tersebut. Kedua, untuk mengetahui urgensi pengesahan UU Tapera terhadap subjek hukum yang terdampak ditinjau dari tercapainya Good Governance. Penelitian ini bersifat yuridis normative dengan pendekatan perundang-undangan dan pendekatan konsep. Hasil penelitian ini menyimpulkan bahwa, pertama, pengelolaan dana UU Tapera diawali dengan tiga tahapan yaitu pengerahan dana, pemupukan dana, serta pemanfaatan dana. Kedua, belum tercapainya beberapa asas dalam perwujudan pelaksanaan Good Governance dalam UU Tapera menyebabkan belum dirasa perlu penerapan undang-undang tersebut.Kata Kunci: Politik hukum; UU tapera; good governance